Antenatal corticosteroids and perinatal outcomes in infants born at 23–25 weeks of gestation. (22nd November 2015) - Goya, M.; Cespedes, M. C.; Camba, F.; Capote, S.; Felipe, A.; Reixachs, A.; Medina, D.; Gorraiz, V.; Pin, S.; Halachian, C.; Gracia, A.; Perapoch, J.; et al.
Abstract: Objectives: T o evaluate the perinatal results of infants born between 23 and 25.6 weeks of gestation. Methods: M edical charts of all women giving birth prematurely (23–25.6 w) from January 2005 to December 2011 were retrospectively reviewed. Cases of malformed infants or deliveries elsewhere were excluded. Results : 198 infants were included. Chorioamnionitis occurred in 86 (43.4%) of the whole group: 26 (86.7%) in the 23-week; 35 (53.8%) in the 24-week and 25 (24.3%) in the 25-week groups. Foetal maturation with antenatal corticosteroids was complete in 119 cases (60.1%): 4 (13.3%) in the 23-week; 35 (53.8%) in the 24-week and 80 (77.7%) in the 25-week groups. Foetal death at birth occurred in 22 cases (11%) and 61 newborns (30.8%) died in the neonatal period. Of the 106 survivors with 2 years complete follow-up, 45 infants (42.4%) did not present sequelae; 16 infants (15.1%) had severe sequelae. A 66.6% (4) of infants born at 23 weeks of gestation did not present sequelae compared with a 32.3% (11) at 24 weeks and 45.4% (30) at 25 weeks. Conclusions : The chorioamnionitis rate was higher when gestational age was lower. The foetal maturation rate was higher when gestational age was higher. A low severe sequelae rate was observed in the whole series, particularly in the 23-week group where the rate was lower than expected; however, these results could have been influenced by the small size of the 23-week group.